IMMATURE PLATELET FRACTION DI DEMAM DENGUE DAN DEMAM BERDARAH DENGUE (Immature Platelet Fraction in Dengue Fever and Dengue Hemorrhagic Fever) - Izzuki Muhashonah; Juli Soemarsono; Puspa Wardhani; Aryati Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Thrombocytopenia is a hematological abnormality found in the majority of Dengue Virus Infection cases with manifestations suchas Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF). Bone marrow response to the decrease in platelets is by increasingthrombopoiesis which can be identified by Immature Platelet Fraction (IPF) examination as an indirect indicator of bone marrow responseto thrombocytopenia. The examination of IPF in venous blood was performed on 29 subjects who met the 1997 WHO criteria, carriedout from January until August 2012. The EDTA blood samples were examined twice, on the day of their admittance and two days later,based on a flowcytometry principle using Sysmex XE-2100. The IPF was derived from the immature platelet ratio against the total numberof platelets (IPF %). The test results were statistically analyzed by using SPSS 20. It was found, that IPF in DHF compared between thefirst and the third day of their admittance was statistically significantly different with p = 0.033 compared to DF with p = 0.444. ThePearson’s correlation showed an inverse correlation between IPF and platelets with r = -0.675 and p = 0.01. The statistical analysisrevealed a significant difference in IPF between moderate- and mild-thrombocytopenia on the first and third day of their admittance withp = 0.014 and 0.001, respectively. Based on this study it can be concluded that IPF can be used to indicate the bone marrow response inboth DF and DHF related to thrombocytopenia.